2013
DOI: 10.2217/fvl.12.138
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Immunomodulatory Approaches in Treating HSV Encephalitis

Abstract: HSV encephalitis (HSE) is the most prevalent sporadic viral encephalitis. Although safe and effective antiviral therapies and greatly improved noninvasive diagnostic procedures have significantly improved outcomes, mortality (~20%) and debilitating neurological sequelae in survivors remain unacceptably high. An encouraging new development is that the focus is now shifting away from the virus exclusively, to include consideration of the host immune response to infection in the pathology underlying development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 120 publications
0
20
0
Order By: Relevance
“…22,24 Previous studies reported that patients with HSE treated with steroids had a better outcome and a rapid decline of cyto-/chemokines. 8,25,26 Similarly, in our acute post-HSE NMDAR case who had longitudinal CSF cytokine analysis, aggressive immunomodulatory treatment with induction and ongoing rituximab, IVIG, and steroids resulted in clinical improvements, and the patient remained well without relapses 18 months after HSE except for mild speech delay. By contrast, the chronic post-HSE cases 2 and 3 were treated latently (many years later) with courses of methylprednisolone, IVIG, and valacyclovir, which resulted in some subjective but marginal improvements.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…22,24 Previous studies reported that patients with HSE treated with steroids had a better outcome and a rapid decline of cyto-/chemokines. 8,25,26 Similarly, in our acute post-HSE NMDAR case who had longitudinal CSF cytokine analysis, aggressive immunomodulatory treatment with induction and ongoing rituximab, IVIG, and steroids resulted in clinical improvements, and the patient remained well without relapses 18 months after HSE except for mild speech delay. By contrast, the chronic post-HSE cases 2 and 3 were treated latently (many years later) with courses of methylprednisolone, IVIG, and valacyclovir, which resulted in some subjective but marginal improvements.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies reported that patients with HSE treated with steroids had a better outcome and a rapid decline of cyto‐/chemokines . Similarly, in our acute post‐HSE NMDAR case who had longitudinal CSF cytokine analysis, aggressive immunomodulatory treatment with induction and ongoing rituximab, IVIG, and steroids resulted in clinical improvements, and the patient remained well without relapses 18 months after HSE except for mild speech delay.…”
Section: Discussionmentioning
confidence: 99%
“…More than 100 organisms can cause viral encephalitis [ 5 ]. HSV was the most common causative virus reported in the United States [ 13 ]. A hospital based study in Taiwan showed that HSV was the predominant pathogen (36%), followed by VZV (13%) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…These viral investigations were confined to 2007 and 2008 making trend analysis of viral AME rather limited. The positive rate of bacteria culture was low, which may be due to the prior antibiotic use or inadequate culture technique [ 13 ].…”
Section: Limitationsmentioning
confidence: 99%
“…We previously reported that ACV protection of susceptible 129S6 (129) mice was reduced when treatment was initiated after day 2 pi because ACV failed to curtail the escalating CNS inflammatory responses [ 28 ]. In contrast, IVIG administered at 24 h pi protected all mice as did ACV [ 17 ].…”
Section: Resultsmentioning
confidence: 99%